Methodology of testability design of electronic components based on the boundary-scan method? - Zhanyong Ren; Dandan Liu; Zhaoyang Zeng (2010 11th International Conference on Electronic Packaging Technology and High Density Packaging, 2010)
The complex electronic components should be tested during either the period of design and manufacture or the period of debugging and running to ensure that their application quality meet the requirements. However, the traditional testing technology encounters tremendous difficulties and the cost of testing is expensive with the rapidly development of the electronic components' integrated technology and the increase of the complexity of their own. Academic research and testing practice indicate that the problem of testing for the electronic components can be predigested and eventually solved no other than improving the testability design of the electronic components. In this paper, at first, the basic principle and the testing flow of the boundary-scan method are introduced. Then, fault models of the electronic components and mathematical model for the boundary-scan test are put forward. Based on the above knowledge, the generation of test vectors and analysis method of the response belonged to the boundary-scan method are introduced in the following. At last, the testability design based on boundary-scan belonged to a complex electronic component is presented.